Evaluasi Kenyamanan Termal Lingkungan Kerja Menggunakan Sistem Monitoring Suhu dan Kelembaban Berbasis Internet of Things (IoT) - Ayu Puspa Wirani; Czidni Sika Azkia; Claudia Shinta Octa Wibowo; Muhammad Faizahassan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Work environment conditions, particularly air temperature and humidity, significantly affect workers’ thermal comfort. Manual monitoring methods often fail to capture thermal fluctuations comprehensively. This study aims to develop an Internet of Things (IoT)-based temperature and humidity monitoring system to evaluate thermal comfort in a workplace environment. The system integrates sensors, a microcontroller, and a communication module to enable real-time monitoring. Collected data were analyzed using the Temperature Humidity Index (THI) to determine comfort categories. Results show that the average temperature ranged from 26.2 to 27.8 °C and relative humidity from 67 to 76%, with THI values between 24.95 and 25.97, indicating moderately comfortable conditions. Higher temperatures were associated with reduced comfort, especially during midday to afternoon periods. The proposed system provides objective, real-time information to support sustainable ergonomics and occupational health and safety based workplace environmental management.